1978
DOI: 10.1093/jnci/61.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infections in Brazil. II. Hodgkin's Disease2

Abstract: Sixty-seven cases of Hodgkin's disease (HD) occurring in São Paulo, Brazil, were studied. Males with HD predominated over females 2.3 to 1. Sixty-six percent of the cases occurred in patients under 30 years of age, 31.7% under 20 years of age, and only 7.5% after 50 years of age. Lymphocyte predominance and mixed cellularity histologic types were most common in patients less than 15 years old, and nodular sclerosis was most common in the 15- to 19-year-old group. Sera from all patients had antibody to the vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Of the eight published studies in which EA antibodies were measured (Table XII), only one study found no difference between cases and controls (Hesse et al, 1977). In the present study, the prevalence of reactivity among cases was higher for EA-R than for D, in agreement with the findings of and of Evans et al, 1978. (Lang et al, 1978 reported that the EA antibodies detected among 27 children with HD were mostly the D component.)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the eight published studies in which EA antibodies were measured (Table XII), only one study found no difference between cases and controls (Hesse et al, 1977). In the present study, the prevalence of reactivity among cases was higher for EA-R than for D, in agreement with the findings of and of Evans et al, 1978. (Lang et al, 1978 reported that the EA antibodies detected among 27 children with HD were mostly the D component.)…”
Section: Discussionsupporting
confidence: 92%
“…A CI that excludes the null value of 1 .O is statistically significant at the 0.05 level. P-values given were obtained by the exact test using Miettinen's tests and methods used have been described previously (Evans et al, 1978(Evans et al, , 1980Henle et al 1971Henle et al , 1974. For the VCA of EBV, an elevated titer was defined as >1:320.…”
Section: Cases and Controlsmentioning
confidence: 99%
“…There are many seroepidemiological studies investigating the relationship between other viruses and HD, but few molecular studies. Serological studies have found no consistent association between herpes simplex virus, varicella zoster virus, cytomegalovirus (CMV), human herpesvirus-7 (HHV-7), rubella, measles and parainfluenza virus (Langenhuysen et al, 1974;Evans et al, 1978;Evans and Gutensohn, 1984;Clark et al, manuscript in preparation). However, elevated antibody titres to human herpesvirus-6 (HHV-6) have been found in HD Biberfeld et al, 1988;Clark et al, 1990), furthermore antibody titres are higher in younger than in older adults and in EBVnegative as opposed to EBV-associated cases (Clark et al, 1990, manuscript in preparation).…”
mentioning
confidence: 99%
“…A few cloning experiments were inconclusive on this point. It is noticeable that most (Levine et al, 1971;Henderson et al, 1973;Hesse et al, 1977) but not all (Evans et al, 1978) studies show elevated titres of serum antibody to members of the herpes virus group in HD patients, whereas these patients have normal titres of antibodies to influenza (Ebbesen et al, 1979) and adenovirus (Hesse et al, 1977).…”
Section: Discussionmentioning
confidence: 99%